PENGARUH LATIHAN VARIASI DRILL TERHADAP KETEPATAN PUKULAN FOREHAND DRIVE ATLET TENIS MEJA PTMSI SUMBAR - Nofa Ella Susanti; Desi Purnama Sari; Jeki Haryanto; Rudyanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low accuracy of the forehand drive stroke among PTMSI West Sumatra table tennis athletes. It aimed to determine the effect of drill variation training on the accuracy of the forehand drive stroke. This study employed a quasi-experimental method using a one-group pre-test and post-test design. The population consisted of 8 athletes, all of whom were selected as the sample using the total sampling technique. The research instrument was a forehand drive stroke accuracy test. Data were analyzed using the normality test, homogeneity test, and the Paired Sample t-test at a significance level of 0.05 with SPSS version 23. The results showed that the mean pre-test score increased from 95.375 to 129.625 in the post-test, with an improvement of 34.25 points. The normality test indicated that the data were normally distributed, while the homogeneity test showed that the data were homogeneous. The Paired Sample t-test yielded a t value of -4.993 with a significance value (Sig. 2-tailed) of 0.002 (< 0.05). Therefore, the research hypothesis was accepted, indicating that drill variation training significantly improved the accuracy of the forehand drive stroke of PTMSI West Sumatra table tennis athletes. The findings are expected to serve as a reference for coaches in developing more effective training programs.